FEKTIVITAS PEMBERIAN KOMBINASI RAGI DAN TAURIN PADA MEDIA KULTUR TERHADAP KEPADATAN POPULASI Daphnia sp. - Islama, Dini; Supriatna, Ahmad; Azra, Muzanni; Nurhatijah, Nurhatijah; Elfianda, Teuku Reza; Suriani, Mai (Universitas Teuku Umar, 2020)
The objective of the present study was to evaluate the giving of baker yeast and taurine mixture in culture media on the population density of Daphnia sp.. The completely randomized design method was used in this study with four treatments and four replications. The treatments studied were the giving of chicken manure 1 g/l as control (P0), the giving of baker yeast and taurine mixture 1 g/l (P1), the giving of baker yeast and taurine mixture 2,5 g/l (P2), and the giving of baker yeast and taurine mixture 4 g/l (P3). Daphnia sp. stocking density was 100 individu/l with the size of 1,5-2 mm. The culture period of Daphnia sp. culture was 16 days. The parameters observed in this study are population density, peak population, and water quality parameters. The ANOVA test showed that the giving of yeast and taurine mix in culture media gave significant effect on the population density of Daphnia sp. Population density of Daphnia sp. the highest was obtained in the treatment of giving 2.5 g / l of baker yeast and taurine mix in cultural media (P2) which is 1320,35 Ind / l with a peak population on the 10th day.